Conceptual competence in medicine: promoting psychosomatic awareness in clinics, research and education - von Boetticher, Dirk (Frontiers in Psychiatry, 2025)
IntroductionIn recent decades, psychosomatic medicine has developed into a distinct specialty, bringing specific clinical concepts to bear seeking to acknowledge the unity (not the identity) of the mind and body in clinical care. Such concepts form the identity of the psychosomatic field as a distinct discipline and its epistemological status between somatic medicine and psychiatry. Despite the importance of these concepts from an educational and a research perspective, too little attention has been paid to their clinical impact.MethodsThis paper investigated the general nature of concepts and their role and significance in structuring the clinical encounter and care, including consideration of their relevance for the hidden curriculum.ResultsConceptual competence is defined as a transformative awareness of the multilayered, fallible, and plural nature of human concepts, which have both descriptive and evaluative and action-guiding properties having both an explicit and an implicit meaning. Conceptual competence in psychosomatic medicine entails dealing competently with the mind–body–distinction and the biopsychosocial model (and criticism of it) with respect to the clinical situation.DiscussionConceptual research is presented as an autonomous research area and the complement of empirical research, having a descriptive and a normative function: descriptively analyzing the concepts we have and normatively searching for the concepts that we need for the integrated care we strive for.